2023
DOI: 10.3390/ijms24021243
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Myeloperoxidase in Clozapine-Induced Inflammation: A Mechanistic Update for Idiosyncratic Drug-Induced Agranulocytosis

Abstract: The risk of idiosyncratic drug-induced agranulocytosis (IDIAG) markedly constrains the use of clozapine, a neuroleptic with unparalleled efficacy. Most clozapine patients experience an early inflammatory response, likely a necessary step in IDIAG onset. However, most patients do not progress to IDIAG, presumably because of the requirement of specific human leukocyte antigen (HLA) haplotypes, T cell receptors, and other unknown factors. We established that clozapine activates inflammasomes and that myeloperoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 95 publications
1
13
0
Order By: Relevance
“…Extracellular vesicles in clozapine-induced inflammation 11 Uetrecht, 2014a;Sernoskie et al, 2022Sernoskie et al, , 2023 that this model recapitulates immune changes observed during the first month of clozapine treatment in patients (Pollmacher et al, 1996;Pollmächer et al, 1997;Löffler et al, 2010;Blackman et al, 2021;Sernoskie et al, 2021). Rats were euthanized by CO 2 inhalation and exsanguination at 3 hours post-injection (n = 6/group).…”
Section: Downloaded Frommentioning
confidence: 81%
See 4 more Smart Citations
“…Extracellular vesicles in clozapine-induced inflammation 11 Uetrecht, 2014a;Sernoskie et al, 2022Sernoskie et al, , 2023 that this model recapitulates immune changes observed during the first month of clozapine treatment in patients (Pollmacher et al, 1996;Pollmächer et al, 1997;Löffler et al, 2010;Blackman et al, 2021;Sernoskie et al, 2021). Rats were euthanized by CO 2 inhalation and exsanguination at 3 hours post-injection (n = 6/group).…”
Section: Downloaded Frommentioning
confidence: 81%
“…Extracellular vesicles in clozapine-induced inflammation 7 et Sernoskie et al, 2022Sernoskie et al, , 2023. Unlike clozapine, the structural analogues olanzapine and fluperlapine did not activate inflammasomes in vitro using a THP-1 macrophage model, as indicated by a lack of caspase-1 activation and release of IL-1β (Sernoskie et al, 2022(Sernoskie et al, , 2023.…”
Section: Downloaded Frommentioning
confidence: 99%
See 3 more Smart Citations